Potential Ways for Fish Biodiversity Conservation Within Siversky Donets Basin in Ukraine Using Cryobiology and Cryobanking Techniques - Ostras, Daniil; Honcharov, Hennadiy; Mikson, Kostiantyn (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):284